The Goldman Dilemma is dead: what elite athletes really think about doping, winning, and death - Woolf, J.; Mazanov, J.; Connor, J. (International Journal of Sport Policy and Politics, 2016)
In the 1980s and 1990s, Goldman`s eponymous `Dilemma` asked if athletes would take a substance that guaranteed sporting glory but killed them in 5 years. The 50% acceptance rate was widely reported as evidence supporting the need for anti-doping policy. Evidence from athletes surveyed in 2011 showed only 1% acceptance. To explore why such striking variation exists, and its implications for policy, this study investigated both the validity and reliability of the original Dilemma and how early twenty-first century elite athletes interpret and understand the Dilemma. The reporting of the original Dilemma demonstrated a lack of scientific rigour, which raises questions about the Dilemma`s status as valid and reliable evidence to inform sports drug control policy. Cognitive interviews with a sample of 30 athletes (30 athletes; 14 female; 19 international; age 22.17 ± 2.13) revealed the death outcome made the Dilemma implausible; it was too absolute an outcome given athletes` non-sporting aspirations (e.g. marriage and parenthood). The idea that a substance could be undetectable and guarantee sporting success was also considered implausible. Athlete conflation of performance enhancement with illegality, immorality and negative health outcomes further undermined perceived plausibility. Thus, the athletes in the sample considered the Dilemma largely implausible. As a consequence of the questionable scientific basis of the original, and the implausibility of the Dilemma to early twenty-first century athletes, the oft-cited 50% acceptance rate is of historical interest only and no longer relevant to drug control policy debate in sport.